(untitled) (Bangladesh Agronomy Journal, 2021)
Crop productivity is greatly affected by drought stress. In order to evaluate the effects of Zn and Fe micronutrients on growth and yield of wheat (Triticum aestivum L.) variety BARI Gom 29, a pot experiment was conducted at the Agronomy research field of Bangabandhu Sheikh Mujibur Rahman Agricultural University during November 2018 to March 2019. Two water regimes i.e. control (80% of field capacity) and drought (40% of field capacity) were maintained throughout the growing season. Micronutrients Zn and Fe viz. i) ZnSO4.7H2O and Fe3SO4.7H2O @22 kgha-1were applied in soil before sowing; ii) ZnSO4.7H2O solution and Fe3SO4.7H2O solution @ 5% of each were applied as foliar spray at flowering stage following completely randomized design (CRD) with three replications. The results indicated that drought stress affected negatively wheat growth such as plant height, fresh weight of leaf, stem, root and total weight of plant as well as yield. Zn and Fe mitigate the drought effects in wheat which ultimately improve the growth and the yield. Among the micronutrients, Fe (Fe3SO4.7H2O) was found more effective when it was applied as foliar spray @ 5% solution for increasing the growth and yield of wheat under water deficit stress condition. Bangladesh Agron. J. 2021, 24(1): 119-128